Pragmatic Randomized Optimal Platelet and Plasma Ratios (PROPPR) Trial: Design, rationale and implementation - Baraniuk, Sarah (2014)
BACKGROUND: Forty percent of in-hospital deaths among injured patients involve massive truncal hemorrhage. These deaths may be prevented with rapid hemorrhage control and improved resuscitation techniques. The Pragmatic Randomized Optimal Platelet and Plasma Ratios (PROPPR) Trial was designed to determine if there is a difference in mortality between subjects who received different ratios of FDA approved blood products. This report describes the design and implementation of PROPPR. STUDY DESIGN: PROPPR was designed as a randomized, two-group, Phase III trial conducted in subjects with the highest level of trauma activation and predicted to have a massive transfusion. Subjects at 12 North American level 1 trauma centers were randomized into one of two standard transfusion ratio interventions: 1:1:1 or 1:1:2, (plasma, platelets, and red blood cells). Clinical data and serial blood samples were collected under Exception from Informed Consent (EFIC) regulations. Co-primary mortality endpoints of 24 hours and 30 days were evaluated. RESULTS: Between August 2012 and December 2013, 680 patients were randomized. The overall median time from admission to randomization was 26 minutes. PROPPR enrolled at higher than expected rates with fewer than expected protocol deviations. CONCLUSION: PROPPR is the largest randomized study to enroll severely bleeding patients. This study showed that rapidly enrolling and successfully providing randomized blood products to severely injured patients in an EFIC study is feasible. PROPPR was able to achieve these goals by utilizing a collaborative structure and developing successful procedures and design elements that can be part of future trauma studies.